Um esboço da história do conceito de trabalho virtual e suas aplicações - Cindra, José Lourenço [UNESP] (Sociedade Brasileira de Física, 2008)
Neste trabalho abordamos a questão concernente à origem do princípio de trabalho virtual e sua consolidação como um dos conceitos fundamentais no estudo da mecânica analítica e, em particular, dos sistemas em equilíbrio estático. Ênfase foi dada às contribuições seminais de Stevin, Galileu e, sobretudo, as de d'Alembert e Lagrange, no tocante ao conceito de trabalho virtual. Além disso, faz-se um comentário geral sobre vínculos holônomos e deslocamento virtual. Alguns exemplos de emprego da equação de d'Alembert-Lagrange são apresentados, para mostrar como o princípio de trabalho virtual pode ser adequadamente aplicado.

In this work is discussed the question concerning the origin and development of the principle of virtual work as a fundamental principle in the study of the analytical mechanics, and particularly of the static equilibrium of an initially motionless system. The seminal contributions of Stevin, Galileo, d'Alembert and Lagrange are emphasized. Furthermore, the concept of holonomic constraints and virtual displacements are presented. Some examples of how to apply the D'Alembert's principle expressed under the D' Alembert-Lagrange equation are introduced, in order to show how this fundamental principle of static and dynamics can be successfully employed.
An outline concerning the history of the concept of virtual work and its applications
Keywords: trabalho virtual; deslocamento virtual; vínculo; princípio d'Alembert; virtual work; virtual displacement; constraint; D'Alembert's principle